Boerhaave's syndrome – a rare cause of retrosternal pain - Kafedžić, Adna (PONS - medicinski časopis, 2021)
Acute chest pain is one of the biggest challenges in diagnostic and therapeutic terms due to a number of differential diagnostic options. Boerhaave's syndrome is a rare condition, but at the same time one of the most lethal diseases of the gastrointestinal tract. For this reason, a high level of suspicion is required in patients with presenting retrosternal pain. Classic symptoms such as vomiting, chest pain, and subcutaneous emphysema may not always be present. The approach to the patient with Boerhaave's syndrome is multidisciplinary. The patient needs urgent rehydration, antibiotic treatment and consultation with a surgery specialist. Treatment is based on the clinical picture of the patient, the location and size of the perforation, but the most important prognostic factor is the time of diagnosis. There are still no official guidelines for the treatment of this condition, and knowledge of treatment options is based on individual case reports from the literature.
Keywords: Boerhaave's syndrome; esophageal perforation; pneumomediastinum; diagnosis